Prevalence and pathogenic potential of Shewanella species in oysters and seawater collected from the Chesapeake Bay and Maryland Coastal Bays - Johnson, Tahirah; Richards, Gary P.; Jacobs, John; Townsend, Howard; Almuhaideb, Esam; Rosales, Detbra; Chigbu, Paulinus; Dasilva, Ligia; Parveen, Salina (Frontiers in Microbiology, 2025)
Shewanella is a genus of Gram-negative marine bacteria with some species associated with human and shellfish illnesses. This study evaluated the abundance of Shewanella species in oysters and seawater from the Chesapeake and Maryland Coastal Bays at four sites between 2019 and 2021. Physicochemical parameters such as temperature, salinity, dissolved oxygen, turbidity, pH, chlorophyll-a, rainfall within the last 48 h, total dissolved solids, and atmospheric pressure were also recorded to evaluate if there was a correlation between environmental parameters and the level of Shewanella. The highest total Shewanella counts were 1.8 × 107 CFU/g in oysters and 4.0 × 102 CFU/mL in seawater. 16S rRNA sequencing was performed on 1,344 representative isolates of which 890 (713 oyster, 177 seawater) were confirmed as Shewanella within 16 species. The top four species isolated from oysters and seawater were S. khirikhana a known shrimp pathogen (49%), S. marisflavi (19%), S. loihica (11%), and S. algae (8%). Testing for alpha and beta hemolysis were performed on all confirmed Shewanella isolates. Beta hemolysis was observed in 405 (46%) of the isolates of which 313 were in oysters and 92 in seawater. In oysters, beta-hemolysis was most prevalent in S. khirikhana (233 of 344 isolates, 68%), while in seawater 64 of 92 isolates (70%) were beta-hemolytic strains. Beta-hemolysis suggests that these could be potentially pathogenic strains. Correlations were performed between physicochemical attributes of the seawater and Shewanella counts. Only seawater temperature and dissolved oxygen correlated with Shewanella counts (r = 0.45 and − 0.41), respectively. No correlations were observed between the physicochemical parameters and Shewanella abundances in oysters. Results suggest that virulent strains of Shewanella may be present in oysters and seawater from the Chesapeake and Maryland Coastal Bays, perhaps as a consequence of rising seawater temperatures.